Practical Management of Chronic Viral Hepatitis - Serviddio, Gaetano (IntechOpen, 2013)
Continuous acquisition of new knowledge in Medicine is essential to ensure progression in diagnostics and therapeutics. In the last decade the discipline of Hepatology has achieved critical progress in the treatment of viral hepatitis. The present book has been realized by a team of experts daily facing clinical problems in the prevention and management of liver diseases and has been designed for a global readership to offer some practical tips to physicians who want update their level of practice in the field. Its a practical volume for daily reference but also an instrument for improving expertise in viral hepatology and discovering the unresolved issues. Management of HBV and HCV hepatitis in young and elderly, HEV hepatitis, evaluation of liver fibrosis, hepatocellular carcinoma, vaccine and prevention and patient education are some of the most important topics covered by the authors. In addition, an outstanding chapter on the skin involvement during viral hepatitis and the tools to manage them during triple therapy is included in the book.